2022
DOI: 10.3390/ijms23137425
|View full text |Cite
|
Sign up to set email alerts
|

G6PD Deficiency Is Crucial for Insulin Signaling Activation in Skeletal Muscle

Abstract: Glucose 6-P dehydrogenase (G6PD) is the first rate-limiting enzyme in pentose phosphate pathway (PPP), and it is proverbial that G6PD is absent in skeletal muscle. However, how and why G6PD is down-regulated during skeletal muscle development is unclear. In this study, we confirmed the expression of G6PD was down-regulated during myogenesis in vitro and in vivo. G6PD was absolutely silent in adult skeletal muscle. Histone H3 acetylation and DNA methylation act together on the expression of G6PD. Neither knock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…These mechanisms, combined with baseline PPP flux, may be sufficient to mitigate ROS in HK-2 cells without additional PPP flux (and subsequent erythritol synthesis). In the skeletal muscle, baseline PPP activity is relatively low compared with other tissues [ 6 , 7 ]. Under oxidative stress, then, a compensatory elevation in PPP flux could explain the observed increase in intracellular erythritol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms, combined with baseline PPP flux, may be sufficient to mitigate ROS in HK-2 cells without additional PPP flux (and subsequent erythritol synthesis). In the skeletal muscle, baseline PPP activity is relatively low compared with other tissues [ 6 , 7 ]. Under oxidative stress, then, a compensatory elevation in PPP flux could explain the observed increase in intracellular erythritol.…”
Section: Discussionmentioning
confidence: 99%
“…It was also recently found that both mouse kidneys and the skeletal muscle respond to high-sucrose intake with elevated erythritol content, whereas the liver maintains a constant erythritol concentration even after exposure to excess sucrose [ 5 ]. Sugar-induced erythritol synthesis in muscle is surprising: in healthy adult muscle, there is relatively little PPP activity, and erythritol synthesis from glucose depends on the PPP [ 6 , 7 ]. Understanding the role of erythritol production in skeletal muscle is important because of the strong contribution of muscle to glucose disposal/homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report of elevated erythritol in skeletal muscle in response to glucose availability (Figure 12C). This was unexpected based on the low expression and activity of pentose phosphate pathway enzymes in skeletal muscle and the relatively low quadriceps erythritol content compared to liver and kidneys (13,26,27). In humans, however, Lustgarten and Fielding recently observed a negative association between skeletal muscle density and serum erythritol levels (25).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, however, Lustgarten and Fielding recently observed a negative association between skeletal muscle density and serum erythritol levels (25). Pentose phosphate pathway enzymes have also been shown to increase in mouse skeletal muscle in response to high-fat diet exposure, and muscle glucose-6-phosphate dehydrogenase (G6PD) expression is associated with impaired glucose metabolism (26,28,29). Historically, increased PPP activity has been reported following skeletal muscle injury and in disordered skeletal muscle (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and colleagues demonstrated that overexpression of G6PD in C2C12 mouse myoblast cell lines results in insulin resistance [ 55 ]. Similar findings were reported by Wang, who linked G6PD overexpression in Wistar rats, induced by a high-fat diet, to enhanced insulin resistance [ 56 ].…”
Section: Role Of Nadph-producing Enzymes In Diabetesmentioning
confidence: 99%